Conception rates in synchronized heifers bred at various times after onset of estrus - DeBenedetti, R.C.; Kiracofe, G.H.; Ward, H.S.; McKee, R.M. (Kansas State University. Agricultural Experiment Station, 2011)
One hundred seven of 112 heifers were in estrus 1 to 5 days after an injection of prostaglandin F2α given when a 7-day synchronization implant was removed. Checks for estrus were made every four hours and heifers were bred 6, 10, 14, 18, 22, or 26 hours after being detected in estrus. Eight heifers were not bred on schedule. Sixty-seven of 99 (67.7%) bred on schedule conceived to first artificial insemination. Conception rates were similar in heifers bred 6 to 26 hours after being detected in estrus, no differences were noted in conception rates between A.M. and P.M. breedings.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Conception rates; Synchronization; Estrus